Impact of Agricultural Technical Efficiency on Farm-Gate Emission: An Implementation of Environmental Kuznets Curve in Asian Developing Countries - Agus Dwi Nugroho (Universitas Sebelas Maret, 2024)
The Environmental Kuznets Curve (EKC) explains that economic activities in developing countries, including agriculture, increase environmental damage. Increased technical efficiency is one approach that is frequently suggested for reducing the negative impacts of farming practices. Unfortunately, there are no studies that investigate this at the macro (national) level. This study examines the impact of technical efficiency on farm-gate emissions in Asian developing countries. Data were collected from 25 developing countries in Asia from 1992 to 2021 and were analyzed using frontiers and the generalized method of moments. The findings demonstrate that technical efficiency is insufficient to prevent increases in CO2, CH4, and N2O emissions. This finding is consistent with the EKC. Gas emissions also rise because of gross domestic product (GDP) and population growth. Human development is the only way to prevent a rise in emissions of these 3 gases. Meanwhile, renewable energy and food prices have varying impacts on CO2, CH4, and N2O emissions reduction. Therefore, based on these findings, it is suggested that developing countries increase the utilization of natural production factors and organic farming, improve human capital development, and conduct a wise selection of renewable energy sources.